Dampak Zakat Produktif Terhadap Pemberdayaan Ekonomi dan Faktor-faktor yang Mempengaruhi Keberhasilan Usaha Mustahiq - Dantes, Raymond (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
This study discusses the effect of the implementation of zakat productive through Mentoring Program implemented Productive Community Empowerment Institute (LPMP) Al-Ansari Agency Amil Zakat (BAZ) Bukittinggi towards economic empowerment mustahik (partner assisted). This study applies qualitative explanatory research design and prove Mentoring Program conducted by the Amil Zakat (BAZ) Bukittinggi through Productive Community Empowerment Institute (LPMP) Al-Anshori have successfully empower and improve the economic conditions mustahik, although the implementation are common obstacles and challenges such as misappropriation of funds by the Society of Productive Potential (MPP), low work ethic Productive Community Potential (MPP) that impact on their business conditions, and the lack of a sense of responsibility and low community awareness Productive Potential (MPP) to pay the installment. Nevertheless, the overall effect on the improvement of productive zakat and income, consumption, savings, investment, productivity, and employment of mustahik such charity.